2023
DOI: 10.1097/bpb.0000000000001102
|View full text |Cite
|
Sign up to set email alerts
|

Mid-term outcomes of temporary medial distal femoral hemiepiphysiodesis with and without medial patellofemoral ligament repair for recurrent patellar instability in skeletally immature patients with genu valgum

Kelly M. Tomasevich,
Adam H. Kantor,
Allan K. Metz
et al.

Abstract: Genu valgum contributes to patellar instability, though outcomes following temporary hemiepiphysiodesis via eight plating are less understood. The purpose of this study was to evaluate the outcomes and need for additional procedures following temporary hemiepiphysiodesis for the treatment of pediatric genu valgum and patellar instability, as well as evaluating the utility of a concurrent medial patellofemoral ligament (MPFL) repair. Patients who underwent medial distal femoral epiphysiodesis for the treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
1
2
0
Order By: Relevance
“…Percentages are reported out of the total 25 patients. performed simultaneous MPFL repair in addition to guided growth, noting that 36% required subsequent procedures for recurrent PFI [40]. Overall, our results align with past literature suggesting good radiographic deformity correction and short-term symptom resolution with simultaneous MPFL and guided growth procedures [22].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Percentages are reported out of the total 25 patients. performed simultaneous MPFL repair in addition to guided growth, noting that 36% required subsequent procedures for recurrent PFI [40]. Overall, our results align with past literature suggesting good radiographic deformity correction and short-term symptom resolution with simultaneous MPFL and guided growth procedures [22].…”
Section: Discussionsupporting
confidence: 86%
“…Ellsworth et al reported correction of genu valgum from 18.8° to 2.7° postoperatively in their patients with PFI, though their outcome data were presented in aggregate amongst all patients with coronal plane angular deformity with various knee pathologies [10]. Tomasevich et al performed simultaneous MPFL repair in addition to guided growth, noting that 36% required subsequent procedures for recurrent PFI [40]. Overall, our results align with past literature suggesting good radiographic deformity correction and short‐term symptom resolution with simultaneous MPFL and guided growth procedures [22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation